(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
With the expansion of social media, the impacts of misinformation on individuals searching for reliable information in the online ecosystem have been worrying. Through a bibliographic review, the article will analyze the main concepts of information disorder discussed in the literature, exploring the limitations behind the individuals’ intentionality in disseminating inconclusive content. In the end, we propose a discussion on the concept of disinformation combined not only with the purpose of the agents, but also with the main effects of the phenomenon on society.